Islamic Education Supporting Women's Empowerment in Ikatan Pelajar Muhammadiyah: Pendidikan Islam Mendukung Pemberdayaan Perempuan di Persatuan Mahasiswa Muhammadiyah - Najla Puteri Aqilla; Asnil Aidah Ritonga (Academia Open, 2025)
General background: Women’s empowerment through Islamic education is essential for strengthening the capacities of female students in formal schooling environments. Specific background: Despite expanded educational access, female students still face barriers such as gender bias, limited participation, and challenges related to digital literacy. Knowledge gap: Previous studies have mainly focused on adult women’s organizations or female Islamic boarding schools, leaving limited research on student-based Islamic organizations as agents of empowerment. Aims: This study analyzes the role of the Muhammadiyah Students Association in empowering female students through Islamic education at SMA Muhammadiyah 02 Medan. Results: The findings show that the organization implements strategic programs including Islamic study sessions for female students, discussion forums, skills workshops, and collaborative religious studies that enhance spiritual, intellectual, social, and leadership capacities. The organization also serves as a platform for gender equality and Islamic character building, although challenges persist such as low active participation, limited resources, and digital vulnerabilities. Novelty: This study offers a new perspective by examining a high school student organization that integrates religious values, leadership development, and digital literacy into its empowerment activities. Implications: The results highlight the strategic role of student organizations in shaping empowered, knowledgeable, and adaptable young Muslim women. Highlights: Highlights the strategic role of student organizations in empowering young Muslim Emphasizes integration of Islamic values, leadership training, and digital Identifies challenges such as low participation and limited organizational Keywords: Islamic Education, Women’s Empowerment, Student Organization, Gender Equality, Leadership Development